Design ethnography : research, responsibilities and futures /: research, responsibilities and futures. (2022) - Pink, Sarah; Fors, Vaike; Lanzeni, Débora; Duque, Melisa; Sumartojo, Shanti; Strengers, Yolande
No abstract available